(untitled) (BIRDEM Medical Journal, 2017)
Background: Sustained low efficiency dialysis (SLED) has been evolved in recent years as technical hybrid of continuous renal replacement therapy and intermittent hemodialysis. It offers optimized hemodynamic stability of the critically ill patients with acute kidney injury (AKI). Our aim was to evaluate the hemodynamic tolerability of SLED in hemodynamically unstable patients with AKI. Methods: This prospective experimental study was conducted in Intensive Care Unit of BIRDEM General Hospital, Dhaka over a period of one year. Results: Forty three hemodynamically unstable patients with AKI were treated with one fifty three sessions of SLED. Mean arterial pressure of the patients before starting dialysis were 80.58±10.92 mmHg and 69.8% patients were on inotrope support. There were no significant differences (p>0.05) in mean arterial pressure during the procedure. No significant changes (p>0.05) occurred in pulse, respiratory rate and temperature during the sessions. Only thirty six out of 153 SLED sessions were associated with complications and hypotension was the commonest one (20.26%). Hypotensive episodes were effectively managed with addition or dose escalation of inotropes. No dialysis had to be discontinued because of hypotension/arrhythmia. Conclusion: SLED is an effective renal replacement therapy for the critically ill patients with AKI which maintains their hemodynamic stability. Birdem Med J 2016; 6(2): 84-90